The antifibrillatory activity study of the compound LMG-124 and lappaconitine hydrobromide on the reperfusion arrhythmias model - V. N. Stolyaruk; I. B. Tsorin; M. B. Vititnova; V. P. Gusev; Yu. I. Murinov; M. S. Yunusov; S. A. Kryzhanovskii (Фармакокинетика и Фармакодинамика)
The antifibrillatory activity comparative study of the compound LMG-124 and the reference drug Lappaconitine hydrobromide was performed on the model of reperfusion arrhythmias. Both drugs are shown to exhibit antiarrhythmic and antifibrillatory activity, but the compound LMG-124 realizes its effect in a significantly lower dose.